Erenumab prevents the occurrence of migraine attacks and not just migraine days: Post-hoc analyses of a phase III study. (October 2021) - Diener, Hans-Christoph; Ashina, Messoud; Ritter, Shannon; Paiva Da Silva Lima, Gabriel; Rasmussen, Soeren; Zielman, Ronald; Tfelt-Hansen, Peer
Background: This post-hoc analysis was conducted to evaluate the effect of erenumab on monthly migraine days, monthly migraine attacks, and attack duration in patients with episodic migraine to investigate whether erenumab actually prevents the occurrence of migraine attacks and/or shortens them. Methods: We conducted a post-hoc analysis of the data from the STRIVE study, in 955 patients with episodic migraine. Relative changes from baseline to mean over months 4, 5 and 6 of the double-blind treatment phase in monthly migraine days, monthly migraine attacks and mean migraine attack duration were assessed. Results: Erenumab reduced monthly migraine days and monthly migraine attacks compared with placebo in a similar way. Erenumab had only a minor impact on shortening the duration of migraine attacks. Conclusion: These post-hoc analyses demonstrate that the decrease in monthly migraine days by erenumab is mainly driven by a reduction in the frequency of monthly migraine attacks and to a much lesser extent by shortening the duration of migraine attacks. Trial registration: This study is registered at ClinicalTrials.gov (NCT02456740)